2003
DOI: 10.1093/molbev/msg175
|View full text |Cite
|
Sign up to set email alerts
|

Birth and Death of Orphan Genes in Rickettsia

Abstract: The origin and evolution of the thousands of species-specific genes with unknown functions, the so-called orphan genes, has been a mystery. Here, we have studied the rates and patterns of orphan sequence evolution, using the Rickettsia as our reference system. Of the Rickettsia conorii orphans examined in this study, 80% were found to be short gene fragments or fusions of short segments from neighboring genes. We reconstructed the putative sequences of the full-length genes from which the short orphan fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 39 publications
0
45
0
3
Order By: Relevance
“…Whereas the degenerative or accelerated evolution of ancestral genes can serve as a mechanism for generating ORFans both in bacteria species undergoing genome reduction (Amiri et al 2003) and in eukaryotes (Domazet-Loso and Tautz 2003), the extreme differences in base composition of ORFans and native genes indicate that this is not the case for ORFans in E. coli. Because all bacterial genomes with G+C contents >30% have intergenic regions that are relatively A+T rich, it has also been suggested that ORFans arise from errors in annotating noncoding regions (Charlebois et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the degenerative or accelerated evolution of ancestral genes can serve as a mechanism for generating ORFans both in bacteria species undergoing genome reduction (Amiri et al 2003) and in eukaryotes (Domazet-Loso and Tautz 2003), the extreme differences in base composition of ORFans and native genes indicate that this is not the case for ORFans in E. coli. Because all bacterial genomes with G+C contents >30% have intergenic regions that are relatively A+T rich, it has also been suggested that ORFans arise from errors in annotating noncoding regions (Charlebois et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…ORFans, particularly those that are short, have been attributed to errors in gene annotation or possibly pseudogenes (Fischer and Eisenberg 1999;Amiri et al 2003;Charlebois et al 2003). One method for determining the functional status of a sequence is by a comparative approach.…”
Section: Orfans Encode Functional Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such coding regions without sequence similarity to other genes in databases are considered orphan open reading frames (ORFs) and termed "ORFans" (12). The origin and function of ORFan genes are still a matter of controversy, with opinions ranging from considering them pieces of junk DNA (1,8,40,44) to seeing them as quickly evolving sequences encoding normally expressed functional proteins (38, 39). Recent clinical evidence raised the possibility that mimivirus might be a human pathogen causing pneumonia (4, 24, 34), as suspected when it was first isolated from a cooling tower following an outbreak of pneumonia (23).…”
mentioning
confidence: 99%
“…However, study of these genes is helpful to aid in the comprehensive understanding of a species. With the increasing development of sequencing technologies, we have gained access to a number of genomes and transcriptomes from a wide range of species, which has aided the extensive study of the LSGs within mammals [8][9][10], insects [2,11,12], fish [13], plants [5,[14][15][16], and microbial species [17][18][19][20]. However, the LSGs in C. elegans have not yet been researched through genomewide methods.…”
Section: Introductionmentioning
confidence: 99%